Evaluation of Bone Healing on Sandblasted and Acid Etched Implants Coated with Nanocrystalline Hydroxyapatite: An In Vivo Study in Rabbit Femur - Lory Melin Svanborg; Luiz Meirelles; Victoria Franke Stenport; Per Kjellin; Fredrik Currie; Martin Andersson; Ann Wennerberg (Hindawi Limited, 2014)
This study aimed at investigating if a coating of hydroxyapatite nanocrystals would enhance bone healing over time in trabecular bone. Sandblasted and acid etched titanium implants with and without a submicron thick coat of hydroxyapatite nanocrystals (nano-HA) were implanted in rabbit femur with healing times of 2, 4, and 9 weeks. Removal torque analyses and histological evaluations were performed. The torque analysis did not show any significant differences between the implants at any healing time. The control implant showed a tendency of more newly formed bone after 4 weeks of healing and significantly higher bone area values after 9 weeks of healing. According to the results from this present study, both control and nano-HA surfaces were biocompatible and osteoconductive. A submicron thick coating of hydroxyapatite nanocrystals deposited onto blasted and acid etched screw shaped titanium implants did not enhance bone healing, as compared to blasted and etched control implants when placed in trabecular bone.